Determination of effective field of application of active methods of vibrations and noise suppression in hydraulic and pneumatic drives - Андренко, Павло Миколайович; Клітной, Володимир Вікторович (Technology audit and production reserves, 2015)
It is analyzed the causes of noise and vibration in the hydraulic and pneumatic drives. It is determined that the main sources of noise and vibrations in such systems are pneumatic or hydraulic sources of energy, the connecting lines. The motor can be identified as a source of mechanical vibration motor. Frequency spectra arising in hydro pneumatic systems are determined. It is shown that in a large number of cases, the fundamental components of noise and vibrations are low frequency. The known passive methods to reduce vibration and noise are considered. It is established that their use for suppressing of low-frequency spectrum is ineffective. A review of active methods of abatement of vibration and noise, performed well when working at low frequencies. Particular attention is paid to compensate for the active devices built on the principles of feedback systems and systems in the perturbation. It is considered the existing developments of active suppress devices of low-frequency noise and vibration in the hydraulic and pneumatic drives, which proved to be effective. It is shown the promising circuit design of such devices and possible areas of its application.